The Relationship of Humanism Thinking with the Concept of Independent Learning and its Impact in the Learning Process - Wewen Andrianto; Ahmad Arifi (Doctoral Program In Elementary Madrasah Teacher Education Faculty Of Tarbiyah And Education - UIN Sunan Kalijaga Yogyakarta, 2025)
Education is developing rapidly as time goes by, becoming a top priority for a country. However, the quality of human resources in Indonesia is still lagging behind compared to several developed countries. To improve the quality of human resources, education must be prioritized. The concept of humanism in education emphasizes the importance of respecting human values ​​and encouraging the humanization process. Meanwhile, the concept of Merdeka Belajar, interpreted as freedom to think, imagine and express, aims to improve the quality of education so that it is superior to before. The relationship between humanist thinking and the concept of Freedom of Learning in the learning context shows that learning must emphasize the process rather than learning outcomes, by involving students as active subjects in the learning process. It is also important to pay attention to the role of the teacher as a facilitator, as well as using learning methods that support the optimal development of students' potential. Learning evaluation must include cognitive, affective and psychomotor aspects, taking into account students' individual development and needs. The method used in this research includes literature analysis and synthesis of relevant ideas to highlight the importance of integrating the concepts of humanism and Freedom of Learning in the educational context in Indonesia.